2009
DOI: 10.1021/jm901577g
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Substituted N,N′-Diarylsulfonamides as Activators of the Tumor Cell Specific M2 Isoform of Pyruvate Kinase

Abstract: The metabolism of cancer cells is altered to support rapid proliferation. Pharmacological activators of a tumor cell specific pyruvate kinase isozyme (PKM2) may be an approach for altering the classic Warburg effect characteristic of aberrant metabolism in cancer cells yielding a novel anti-proliferation strategy. In this manuscript we detail the discovery of a series of substituted N,N′-diarylsulfonamides as activators of PKM2. The synthesis of numerous analogues and the evaluation of structure activity relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 27 publications
3
101
0
Order By: Relevance
“…One way is using PKM2 activators to increase its enzyme activity to restore glycolytic flux from PEP to pyruvate so that less 3-PG accumulates. Currently there are PKM2 activators under development (40,41). The present studies also suggest that an alternative strategy might be to develop drugs that inhibit one of the enzymes in the serine synthetic pathway.…”
Section: Discussionmentioning
confidence: 68%
“…One way is using PKM2 activators to increase its enzyme activity to restore glycolytic flux from PEP to pyruvate so that less 3-PG accumulates. Currently there are PKM2 activators under development (40,41). The present studies also suggest that an alternative strategy might be to develop drugs that inhibit one of the enzymes in the serine synthetic pathway.…”
Section: Discussionmentioning
confidence: 68%
“…We screened a library of fragment-like small molecules (1,767 compounds), with molecular weights ranging from 150 to 300 Daltons, for PKM2 activators using a coupledbiochemical assay with a luminescent readout (23). A number of PKM2 activators were identified with AC 50 values ranging from 20 to 100 mmol/L, and maximal activation levels similar to FBP.…”
Section: Resultsmentioning
confidence: 99%
“…In light of such evidence, efforts have focused on the discovery and development of small-molecule PKM2 activators. There are several examples of small molecules that activate PKM2 in biochemical assays (23)(24)(25), and recent reports have shown that PKM2 activators affect cancer cell growth in vitro and tumor growth in vivo (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that activation of PKM2 to restore the high pyruvate kinase activity state found in normal tissues may be an alternative strategy to target the pyruvate kinase step in cancer. Isoform--specific small molecule activators of PKM2 have been reported 103,104 . Whether these compounds can induce the same growth disadvantage in vivo that is observed in PKM1--expressing cells remains to be determined.…”
Section: --Deoxyglucose (2dg) Is An Inhibitor Of Glucose Metabolism mentioning
confidence: 99%